Pengaruh Komponen Arus Kas dan Laba Kotor terhadap Harga Saham (Studi Kasus pada Perusahaan Manufaktur Sub Sektor Otomotif dan Komponen di Bursa Efek Indonesia Tahun 2013-2017) - D Delvianti; Melli Herfina; Yessi Rinanda (SAFE-Network, 2023)
The purpose of this study was to analyze the effect of cash flow components and gross profit on stock prices. The population in this study is the automotive sub-sector and components listed on the Indonesia Stock Exchange (IDX) in the 2013-2017 period. The sampling method used is the purpose sampling method with a sample of 8 companies for 5 consecutive years of observation so that the total sample is 40. The method of analysis in this study uses multiple linear regression. The results of this study indicate that operating cash flow and gross profit have no significant effect on stock prices. Meanwhile, investment cash flow and financing cash flow have a significant effect on stock prices. Meanwhile the cash flow components (operations, investment, funding and gross profit) have a simultaneous effect on stock prices.